CONCRETOS DE VANGUARDIA: Manteniendo a Sonora líder en la Industria alimentaria - Casas Félix, Vladimir (UNIVERSIDAD DE SONORA, 2018)
Sonora is a state with a enviable food industry, because despite of weather conditions, droughts and water disputes between the northern and southern parts of the state, its agri-livestock industry has stood out in the country.  This is the reason why the professionals that design and build these industry’s buildings must provide high quality facilities that reach their whole usable life, generating durable, functional and innocuous spaces. Nevertheless, given the activities and high organic content of  the handled agri-livestock products and the necessity to preserve them frozen at very low temperatures and with high quality and cleanliness standards, this is a significant challenge, including, on top of all,  selecting materials capable of resisting these duty conditions. Keeping at the leading-edge in durable products and building processes is imperative in order to not to be out of this economy sector of the country and specifically of the state of Sonora, context that is addressed in this article.